Harmonisasi Hukum Islam dan Pancasila Dalam Menangani Kasus Terorisme di Indonesia - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Dista Suryana Putri; Rindi Rahayu; Teuku Ardhan Wardhana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Handling terrorism cases in Indonesia requires a careful approach considering the diversity of applicable legal sources, especially Islamic Law and Pancasila. This article explores harmonization efforts between the two legal systems in the context of countering terrorism. Islamic law, with its principles that emphasize justice, security and protection of society, offers an approach based on restoration and enforcement of social norms. On the other hand, Pancasila as the basis of the state and national ideology provides a normative framework that emphasizes unity, social justice and human rights. This study analyzes how the principles of Islamic law can be integrated with the Pancasila legal framework to create an effective legal system in dealing with terrorism. The research focus includes a review of existing laws and regulations, policies for handling terrorism, as well as the implementation and implementation of the law in practice. This article also identifies challenges that may arise in the harmonization process, including potential conflict of norms and differences in interpretation between Islamic Law and Pancasila. This study aims to provide strategic recommendations for policy makers and law enforcement officials to create a more holistic and harmonious approach in dealing with terrorism. It is hoped that the integration of the values of Islamic law with the principles of Pancasila can strengthen efforts to prevent and overcome terrorism, as well as maintain the diversity and unity of the nation. Thus, this research contributes to the development of legal policies that are more inclusive and fair, in accordance with the Indonesian social and cultural context.